Effect of Coconut Husk Liquid Organic Fertilizer on the Vegetative Growth of Bird’s Eye Chili (Capsicum frutescens) - Riyadi, Afwan; Alibasyah, Lestari M.P.; Febriani, Vita Indri; Lilies,; Shamdas, Gamar B.N.; Agni, Raya (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the effectiveness of liquid organic fertilizer (LOF) derived from coconut husk on the vegetative growth of bird’s eye chili (Capsicum frutescens) using a completely randomized design (CRD). The experiment consisted of five treatment levels with four replications, resulting in a total of 20 experimental units. The treatments included P0 (control), P1 (10%), P2 (15%), P3 (20%), and P4 (25%), each applied at a volume of 250 mL per application on 14, 28, and 42 days after planting. Plant height and the number of leaves were measured at 21, 35, and 49 days after planting. The data were analyzed using normality and homogeneity tests, analysis of variance (ANOVA), and the least significant difference (LSD/BNT) post hoc test. The results demonstrated a highly significant effect of coconut husk-based LOF application, with p-values of 0.002 for plant height and <0.001 for the number of leaves. Among the tested treatments, the 15% LOF concentration (P2) exhibited the most optimal effect in promoting the vegetative growth of bird’s eye chili.